Effect of irrigation application on soil and land productivity of wheat under semi-arid environment - Bhatti, Muhammad Tousif; Sarwar, M.K; Tahir, A.A.; Yar, M. (2017)
A study was conducted in Sargodha, Pakistan during the year 2011 to testify irrigation practices as a method for reclaiming salt affected soil. Field experiments were conducted on saline-sodic and uncultivated land divided into 12 field plots. Six irrigation treatments, each replicated on two field plots, were applied to test the responses of soil and wheat crop yield. Six irrigation treatments combined two variables: (i) source of irrigation (canal water, brackish groundwater and mixed in 50:50 proportion) and (ii) irrigation scheduling (fixed-rotation or Traditional Warabandi (TWB) and 75% management-allowed depletion (MAD)). The electrical conductivity (ECe) and sodium adsorption ratio (SAR) of saturated paste extracts of soil were observed at four depth intervals ranging from zero to 90 cm during the four crop growth stages. Only top 15 cm soil layers of field plots could be reclaimed upto the permissible ECe level of < 4 dS/m where canal water was applied for irrigation. In deeper layers (31 to 90cm) the ECe increased from the ambient levels in response to irrigation treatments. The crop yield (wheat grains in kg/ha) was measured from all individual field plots. Canal water application with 75% MAD scheduling proved to be the optimum treatment giving average yield of 1265 kg per hectare while the treatment with groundwater application under TWB showed the lowest average yield (435 kg/ha).